2006
DOI: 10.1002/jor.20011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of experimental suprascapular nerve block on active glenohumeral translations in vivo

Abstract: Static superior shoulder instability is associated with long-standing rotator cuff tears. Factors or mechanisms which can prevent superior migration of the humeral head, and therefore allow preservation or restoration of shoulder function despite nonanatomical cuff repair, are poorly understood. The question has therefore arisen, whether centering of the humeral head was the result of active shoulder muscle function. It was the goal of this experimental investigation to (1) determine the pattern of glenohumera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
2
12
0
1
Order By: Relevance
“…This is in accordance with a previous model for which the joint reaction force fell close to the superior border of the glenoid from 301 to 451 of glenohumeral abduction (Poppen and Walker, 1978). Resting muscle tone (Debski et al, 1999a;Schiffern et al, 2002), intraarticular pressure (Itoi et al, 1993) or subacromial spacer effect of the supraspinatus (Werner et al, 2006) might already be sufficient to confine these humeral head translations. After 601 of elevation, the deltoid becomes a stabilizer with a line of action approaching a perpendicular line to the glenoid surface (Ackland and Pandy, 2009).…”
Section: Discussionsupporting
confidence: 86%
“…This is in accordance with a previous model for which the joint reaction force fell close to the superior border of the glenoid from 301 to 451 of glenohumeral abduction (Poppen and Walker, 1978). Resting muscle tone (Debski et al, 1999a;Schiffern et al, 2002), intraarticular pressure (Itoi et al, 1993) or subacromial spacer effect of the supraspinatus (Werner et al, 2006) might already be sufficient to confine these humeral head translations. After 601 of elevation, the deltoid becomes a stabilizer with a line of action approaching a perpendicular line to the glenoid surface (Ackland and Pandy, 2009).…”
Section: Discussionsupporting
confidence: 86%
“…40 Although it is generally believed that loss of rotator cuff strength will result in increased GHJ excursion and superior translation of the humeral head, this belief is based on cadaveric studies that are unable to accurately simulate muscle forces and joint forces. Indeed, recent in vivo studies have suggested that paralysis of the supraspinatus and infraspinatus muscles results in neither superior migration of the humerus 65 nor an increase in subacromial space pressure. 64 Thus, rotator cuff weakness may not necessarily result in superior humeral translation and could instead result in the humeral head translating inferiorly relative to the glenoid.…”
Section: Discussionmentioning
confidence: 99%
“…19 In case of an even number of images, the one with the larger amount of glenoid depiction was chosen. This assured that all investigators used the same anatomic references and measured the shortest distance between the undersurface of the acromion and the top of humeral head on similar slices where the humeral head had its maximal superoinferior diameter.…”
Section: Methodsmentioning
confidence: 99%